Агрегирование математической модели электронной схемы на основе принципа сжимающейся области адекватности - Прасол, И. В. (Інститут електродинаміки НАН України, 2010)
The method of obtaining aggregated mathematical models of analog electronic circuits based on the principle of shrinking the area of the adequacy and assessing the adequacy of using the methods of interval analysis is considered. This enables us to dynamically control the dimension and the error model at the stage of its synthesis.
Keywords: mathematical model aggregation , electrical analysis, analog electronic circuit, adequacy of a model, CAD.